Virtual Reality-Based Learning Innovations in Early Childhood Education - Benteng Martua Mahuraja Purba; Basuki Wibawa; Eveline Siregar; Ronald Sianipar; Dewi Lidya S (STAI Hubbulwathan Duri, 2024)
Early Childhood Education (PAUD) in Indonesia is designed for children under six to foster learning motivation and interest. However, young learners often focus more on play than education. Virtual reality (VR)-based learning offers innovative opportunities to enhance learning experiences and deepen material comprehension. This study utilizes a qualitative approach through a Systematic Literature Review (SLR) of articles published in Indonesian journals. Primary data are derived from literature on virtual reality-based educational innovations aimed at increasing early childhood interest in learning. The findings reveal that virtual reality significantly enhances learning interest among early childhood learners compared to traditional methods. VR-based learning also improves educational outcomes, memory retention, and student engagement. These outcomes demonstrate the effectiveness of VR as a tool for stimulating curiosity and motivation in early learners. The study highlights the potential of virtual reality in early childhood education and its role in transforming traditional learning methods. By integrating VR, educators can create immersive and engaging experiences that align with the developmental needs of young learners. The findings emphasize the need to develop VR infrastructure and encourage its adoption in PAUD schools across Indonesia. The study advocates for educators to embrace VR technology to enrich early childhood learning, ultimately fostering greater interest and engagement among young learners.